The Design of Augmented Reality Application as Learning Media Marker-Based for Android Smartphone - Ambarwulan, Diah; Muliyati, Dewi (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2016)
Abstract This preliminary study focused on the technique of instructional media that is integrated with Augmented Reality to increase the interest of studies student. This study uses the book as a medium that brought information representing a 3D model of the atom objects. This paper emphasizes the techniques of designing learning media in the form of Augmented Reality applications to be used on smartphones with the Android Operating System. Keywords: Augmnted Reality, 3D Model, Android Abstrak Penelitian pendahuluan ini difokuskan pada teknik perancangan media pembelajaran yang diintegerasikan dengan Augmented Reality untuk meningkatkan minat pelajar. Penelitian ini menggunakan buku sebagai media yang memunculkan informasi model 3D yang merepresentasikan objek atom yang sesungguhnya. Paper ini menekankan pada teknik merancang media pembelajaran berupa aplikasi Augmented Reality untuk digunakan pada smartphone dengan Operating System android. Kata-kata kunci: Augmented Reality, Model 3D, Android